THE TEACHING METHOD USED BY THE LECTURER IN TEACHING WRITING COURSE - Rezky Uspayanti (KOLONI, 2022)
The teaching method is one of the important aspect in achieving learning objective. The teaching method used as the way to attract the interest in learning. The purpose of this research was finding out the teaching method used by the lecturer in writing subject that focused on paragraph writing. This research was done in Musamus University exactly in writing class. This research was qualitative method that the data was taken through interview. The result of interviews was analyzed in qualitative by descriptive form. The result of this research namely there were three kinds of teaching method used namely inquiring method, clustering method, and task-based learning method. The lecturer reasons using the methods in teaching because the methods could help the students to understand the paragraph writing and made students more active in learning.   Keywords: Teaching method, teaching writing, paragraph writing